2010
DOI: 10.1007/s00104-009-1861-2
|View full text |Cite
|
Sign up to set email alerts
|

Zystische Tumoren des Pankreas

Abstract: Cysts of the pancreas most often develop after chronic or acute inflammation of the pancreas. Cystic neoplasia of the pancreas have been increasingly recognized in clinical practice and 90% are represented by four types: serous microcystic (SCN), mucinous cystic (MCN), intraductal papillary-mucinous (IPMN) and solid pseudopapillary (SPN) neoplasia. IPMN is the most common form nowadays and main duct and branch duct types can be differentiated by morphology. This classification is of prognostic and therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The accurate prevalence of MCN is difficult to assess; a recent publication by Valsangkar et al reported about 23% of MCN in patients with resected cystic tumors of the pancreas [84]. MCNs mainly occur in women and are typically located in the pancreatic body and tail [42, 60, 85, 86]. These cystic lesions are almost solitary and the vast majority of MCNs are asymptomatic and found incidentally [15].…”
Section: Mucinous Cystic Neoplasm (Mcn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate prevalence of MCN is difficult to assess; a recent publication by Valsangkar et al reported about 23% of MCN in patients with resected cystic tumors of the pancreas [84]. MCNs mainly occur in women and are typically located in the pancreatic body and tail [42, 60, 85, 86]. These cystic lesions are almost solitary and the vast majority of MCNs are asymptomatic and found incidentally [15].…”
Section: Mucinous Cystic Neoplasm (Mcn)mentioning
confidence: 99%
“…Because, in particular, MCNs mainly occur in young patients and are mostly located in the body and tail of the pancreas, resection is the most appropriate and reliable treatment [42, 50]. …”
Section: Mucinous Cystic Neoplasm (Mcn)mentioning
confidence: 99%